Subclinical hypothyroidism and Down's syndrome; studies on myocardial structure and function. Issue 11 (11th November 2003) - Toscano, E; Pacileo, G; Limongelli, G; Verrengia, M; Di Mita, O; Di Maio, S; Salerno, M; Del Giudice, E; Caniello, B; Calabrò, R; Andria, G
Abstract : Background: The management of subclinical hypothyroidism (SH) is still controversial, as the benefit to risk ratio of prolonged l -thyroxine therapy is not clear cut. Some authors have shown abnormalities of myocardial function and structure in adults with SH, which could be reversed by l -thyroxine therapy. As SH frequently affects children with Down's syndrome (DS), and almost one half of these are affected by congenital heart disease, a concomitant SH related impairment of cardiac function might further compromise their clinical condition. Aims: To establish whether SH influences myocardial structure and function in children with DS. Methods: Sixteen children with DS and untreated SH and 25 matched euthyroid controls with DS underwent echocardiographic analysis of left ventricular mechanics and tissue characterisation. Results: None of the 16 patients had myocardial impairment. Conclusion: Results suggest that children with DS who have SH are not at risk of cardiac disease. Clinicians should consider these data in the management of SH, as the benefit to risk ratio of prolonged l -thyroxine therapy is not clear cut.